Strategi Pengembangan Air Terjun Pengempu Sebagai Wisata Alam di Desa Wisata Cau Belayu Kabupaten Tabanan Bali - Sarastiawan, I Kadek; Prayogi, Putu Agus; Putri , Komang Shintya Nita Kristiana (Jurnal Mosaik Hospitaliti, 2022)
The purpose of this research is to define the ability of Pengempu Waterfall tourism and analyze the energy development strategy to achieve Pengempu Waterfall as a natural tourism in Cau Belayu Hamlet. The information collection methods used are monitoring, question and answer, selection and SWOT analysis to define tourism capabilities and to formulate a strategy for the development of tourism in the Reservoir Water. The information analysis method used is a SWOT analysis method, which is to analyze internal aspects (strengths and weaknesses) and external aspects (opportunities and dangers) with the encouragement of the SWOT matrix. The results of this research show that the strategy used in the development of Air Turun Pengempu as a natural tourism in Cau Belayu Darmatourism Hamlet is the ability of 4 A, (attraction, amenity, accessibility and ancillary), with the position of stakeholders who help the development of tourism in Air Turjun Pengempu using a SWOT strategy of power, weakness, opportunity and danger.